HISK Laureaten = Laureates 2006. - Hisk (Hoger Instituut voor Schone Kunsten), Antwerpen; Arkesteijn, Roel; Elias, Willem; Lumpkin, Libby; Martens, Hans (Antwerpen Gent : HISK (Hoger Instituut voor Schone Kunsten) Antwerpen HISK (Hoger Instituut voor Schone Kunsten) Gent, 2006)
Avila, Plinio ; Bellinckx, Ruben ; Claes, Sara ; Declercq, Koert ; El Gholabzouri, Mohand ; Geerts, Bart ; Goetschalckx, Wannes ; Haines, Elisabeth ; Hinrichs, Heide ; Kindermans, Ruben ; Klimová, Barbora ; Leech, Adam ; Paetau, Kristofer ; Riemis, Dimitri ; Timmermans, Ante ; Wright, Cindy
biog., prijzen, tent. p. 149-154
Publicatie n.a.v. tentoonstelling "Hisk, In/Out" in Antwerpen, 02.12.2006 - 17.12.2006
Engels
Nederlands
boek